Marketing Mix and Trust as A Visiting Intention Factors - Hasyim Hasyim; Rina Mutiara; Herwatt Setiawan (Penerbit Kemala Indonesia, 2020)
Patient’s visit plays an important role in the sustainability of hospital services. Patient’s decision to visit could be measured through patient visiting intention which is influenced by marketing mix and trust. This research aimed to gather empirical proof in order to describe the relationship between marketing mix and visiting intention through trust as an intervening variable. The 200 respondents from patients in outpatient clinic of Hospital X are proposed in this study. Thus, this research is quantitative with causality method was conducted with 4-interval-scale questionnaire. All the data was analyzed with Structural Equation Modelling. Here, most of the respondents in this study are female which is in the age 21 to 30 years old also graduated from senior high school and vocational school. In addition, the female respondent in the age 21 to 30 did not use insurance to cover their bill while an old patient was visiting general practitioner clinic. Here, the descriptive analysis shows that marketing mix and visiting intention are in moderate category while trust is in high category. The results of this study indicate that there is effect of marketing mix on visiting intention through trust. The effect of marketing mix on trust and trust on visiting intention are positive and significant while the direct effect of marketing mix on visiting intention is negative and significant. Thus, in this study found that trust is intervening variable and marketing mix has a negative effect on visiting interest.